Mozambique : van kolonie tot onafhankelijkheid - Bosgra, Sietse; Kroef, Marja; Roskam, Karel; Fonte, Arthur; Van Waesberge, Robert (Bussum: Agathon, 1974)
"Sietse Bosgra, Marja Kroef, Karel Roskam, Arthur Fonte, Robert van Waesberge"